Biosafety and Biosecurity in Containment: A Regulatory Overview - Beeckman, Delphine S. A.; Rüdelsheim, Patrick (Frontiers in Bioengineering and Biotechnology, 2020)
When biosafety for contained use is addressed in international fora and discussions, often the topic is limited to working with genetically modified organisms (GMOs) in facilities such as laboratories, animal facilities and greenhouses. However, the scope of biosafety in containment encompasses many other types of biological materials, such as human, animal & plant pathogens, nucleic acids, proteins, human samples, animals or plants, or by-products thereof, and overlaps often with the topic of biosecurity. This is also reflected in the regulations that apply for activities with biological materials in contained facilities. The common denominator of these regulations is the focus on protection of people and environment, while applying the key principles of risk assessment and risk management. This review provides an overview of regulatory frameworks for biosafety and biosecurity in containment around the globe, as well as points out overlap with other regulatory frameworks, such as the Nagoya Protocol, or Plant & Animal Health regulations.